A MODEL OF POINT-TO-FACE CONTACT FOR THREE-DIMENSIONAL DISCONTINUOUS DEFORMATION ANALYSIS - Jiang Q.H.; Yeung M.R. (My University, 2004)
The key to three-dimensional discontinuous deformation analysis (3D DDA) is a rigorous contact theory that governs the interaction of many three-dimensional blocks. This theory must provide algorithms to judge contact types and locations and the appropriate state of each contact, which can be open, sliding or locked. This paper presents a point-to-face contact model, which forms a part of the contact theory, to be used in 3D DDA. Normal spring, shear spring and frictional force submatrices are derived by vector analysis and the penalty method. Also given are the "open-close" iteration criteria and operations performed for different changes in contact state. Sliding at a contact can occur in any direction parallel to the contact face, as opposed to one of two directions in two-dimensional DDA. This point-to-face contact model has been implemented into a 3D DDA computer program, and numerical results from several test cases demonstrate the validity of the model and the capability of the program.
Keywords: 3D DDA; POINT-TO-FACE CONTACT; OPEN-CLOSE ITERATION